PROJECT TOKBUK – “Katok Para sa Magandang Bukas”: An Effective Educational Strategic Approach for Out-of-School Youth in Valenzuela City - Avante, Nickolai Corro; Valle, Czarina Kaye Sanchez; Rentillo, Ronald Velasco (International Journal of Research in Interdisciplinary Studies, 2025)
This research paper examines the effectiveness of PROJECT TOKBUK – “Katok Para sa Magandang Bukas” as an educational strategic approach for out-of-school youth (OSY) children in Valenzuela City, Philippines. The program is designed to address the challenges faced by OSY children in accessing education due to poverty, lack of parental support, and other socio-economic factors. The study employs a mixed-methods approach to evaluate the program's impact. The research findings indicate that PROJECT TOKBUK – “Katok Para sa Magandang Bukas” is an effective educational strategic approach for OSY children in Valenzuela City. The program's holistic approach, community-based outreach program, and partnership with local government agencies and private organizations have contributed to its success. The program has provided OSY children with the necessary education and life skills training to improve their quality of life and prospects. The program has also contributed to the reduction of crime rates in the community. The study highlights the importance of community-based outreach programs in addressing the educational needs of OSY children. It also emphasizes the need for partnerships between local government agencies, private organizations, and community-based organizations to provide the necessary resources and support needed to sustain such programs. The research paper concludes by recommending that similar educational strategic approaches be implemented in other communities facing similar challenges. The study underscores the importance of providing education and life skills training to OSY children as a means of breaking the cycle of poverty and improving their prospects.